2017
DOI: 10.1016/j.ajog.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metachronous ovarian cancer after ovarian conservation in young women with stage I cervical cancer

Abstract: Metachronous ovarian cancer risk after ovarian conservation for women with stage I cervical cancer is <1%. Older age, non-white ethnicity, adenocarcinoma or adenosquamous histology, and adjuvant radiotherapy may be associated with an increased metachronous ovarian cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…2 Data sparsity means that the number of observations is very low in the combinations of independent and dependent variables. As indicated by Matsuo et al 1 in Tables 3 and 4, there are not enough events in their study, and data sparsity was expected. Sparse data bias is one of the most important biases that occur in studies with sparse data and makes the measure of association remarkably inflated and the confidence interval considerably wide.…”
Section: To the Editorsmentioning
confidence: 84%
See 2 more Smart Citations
“…2 Data sparsity means that the number of observations is very low in the combinations of independent and dependent variables. As indicated by Matsuo et al 1 in Tables 3 and 4, there are not enough events in their study, and data sparsity was expected. Sparse data bias is one of the most important biases that occur in studies with sparse data and makes the measure of association remarkably inflated and the confidence interval considerably wide.…”
Section: To the Editorsmentioning
confidence: 84%
“…We were interested to read the article authored by Matsuo et al 1 that was published in the American Journal of Obstetrics and Gynecology in 2017. The authors conducted research to explore the incidence of and risk factors for metachronous ovarian cancer among young women with stage I cervical cancer who had undergone ovarian conservation at the time of hysterectomy.…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the excess risk of secondary malignancy in women with cervical cancer due to various factors such as cigarette and radiotherapy uses, long‐term safety assessment after ovarian conservation is particularly necessary; however, this was not applicable in our retrospective study with relatively short follow‐up (median follow‐up time, ∼5 years). A recent population‐based study has shown that 10‐ and 20‐year cumulative incidences of metachronous ovarian cancer after ovarian conservation for young women with stage I cervical cancer are 0.2 and 0.5%, respectively (median follow‐up time, >10 years) . Because their study did not have a proper control arm from general population to estimate relative risk of ovarian cancer after ovarian conservation for young women with stage I cervical cancer, further study is warranted to assess this long‐term safety issue after ovarian conservation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study has shown that 10-and 20-year cumulative incidences of metachronous ovarian cancer after ovarian conservation for young women with stage I cervical cancer are 0.2 and 0.5%, respectively (median follow-up time, >10 years). 40 Because their study did not have a proper control arm from general population to estimate relative risk of ovarian cancer after ovarian conservation for young women with stage I cervical cancer, further study is warranted to assess this long-term safety issue after ovarian conservation.…”
Section: Cancer Therapy and Preventionmentioning
confidence: 99%